Optimizing frontal polymerization of different epoxy resins for magnetocuring - Tay, Jerry Rong Yao (Nanyang Technological University, 2022)
Classical curing of epoxy resin requires two-part mixing of epoxy and hardener, which is a laborious and time-consuming process. It is also an energy-inefficient process as the formulation requires it to be heated and maintained at a high temperature to attain complete polymerization. Some of the shortcomings of the classical curing method have been overcome by a recently developed strategy known as frontal polymerization by which, the curing of the epoxy resin is achieved through the activation of a localized reaction zone. The curing reaction at the localized zone can be triggered through UV-light or heat activation. The heat generated due to the epoxy polymerization reaction helps the curing wave propagate in all directions without requiring any additional energy. It has also been hypothesized that frontal polymerization can be triggered through the localized heating of curie nanoparticles under a magnetic field. In this study a structure relationship study of three epoxy monomers, two onium salts and five thermal initiators will be explored, aiming to optimize the curing temperature required for frontal polymerization. This optimized curing condition will be applied in future for magnetic field stimulated curing of epoxy resins.